Using the Past to Prepare for the Future: A 2018 Pilot Study to Improve the Hospital Response for Mass Casualties via a Multi-Dimensional Approach. Issue Volume 34:Issue s1(2019) (May 2019) - Contreras, George W.; Pohlman, Kevin; Mandel-Ricci, Jenna; Markenson, David; Reilly, Michael
Abstract : Introduction: Recent mass shooting events remind us of the importance of hospitals' preparedness to manage a large number of patients in a short period of time. While prehospital systems triage for field interventions and priority of transport, they were not designed to triage for the scarce resources of a hospital. Therefore, upon arrival to hospital, clinicians must then quickly determine how to best assess and provide life-saving interventions based on their limited resources. Methods: In collaboration with the Greater New York Hospital Association (GNYHA), the Center for Disaster Medicine at New York Medical College piloted an interactive and intensive eight-hour course at four New York State hospitals that covered critical areas such as: current literature on Mass Casualty Events and Triage, review of hospital emergency management, hospital-based triage principles, a MCI exercise in the emergency department, a surge capacity tabletop exercise, and use of ultrasound. While targeted towards physicians to foster team-based care and learning, nurses, physician assistants, and hospital administrators also participated in the pilot course. Results: Sixty persons from four hospitals participated in the pilot phase. Preliminary findings post-training reveal the following: 58% of participants expressed greater confidence in distinguishing between emergency department triage and triage during disasters; 59% of participants expressed greater confidence in performing initial triage of victims; 49% of participants expressed greater confidence in describing the use of ultrasound-guided triage; and 95% of participants reported an enhancement in their ability to perform their clinical role. Discussion: Preliminary findings reiterate the ongoing need for hospitals to provide training to their staff in the unique aspects of hospital triage and surge management using tools specifically designed in order to be prepared for the rapid influx of a large number of patients. A multipronged training model is a positive approach to help hospitals prepare for large-scale disasters.